Characteristics Of Gerund Use in English Media Texts - Nabiyev Mashrab Abduvaitovich (Euro Asian Journal Publishing, 2024)
The article deals with the study of the characteristics of gerund usage in media texts in English. Since media texts are also nature-word art, its main element is the word and language in general. There is no doubt that the artistic maturity of any media text depends on the ability of the writer to express it artistically using various linguistic content. Media texts, sometimes in verse or in prose, have their own language, which uses colorful words, syntactic structures and linguistic elements, speech devices to create an emotional, mental, and visual effect on the reader. and will have a psychological impact.
Keywords: media linguistics; media texts; media language